THE REFLECTION OF PRONUNCIATION TEACHING MATERIALS: AN OLD PARADIGM IN A NEW ERA - Agis Andriani; Fuad Abdullah; Yuyus Saputra (Siliwangi University, 2017)
Ideally, pronunciation teaching materials should be developed based on the equal proportion of segmental and suprasegmental features and the employment of innovative pronunciation learning task types (e.g. awareness-raising tasks, rhyme and verse, ear training, etc.) (Goodwin, 2013). Unfortunately, such a reasonable breakthrough apparently has not responded by the effective use of pronunciation teaching materials. For these reasons, this study was aimed at exploring the pronunciation teaching materials in Pronunciation Practice module and course syllabus at a university in Tasikmalaya, Indonesia. The data were analyzed with Tergujeff’s data-driven classification (2010), namely phonetic training, reading aloud, listen and repeat, rhyme and verse, rules and instructions, awareness-raising activities, spelling and dictation and ear training. The findings revealed that the existing pronunciation teaching materials only accentuated on fostering the students’ segmental features. Besides, the traditional task types still dominated the tasks in such a module, such as phonetic training, reading aloud, listen and repeat and rules and instructions. This confirms that the creative and dynamic use of current pronunciation teaching materials enable the students not only to undergo accuracy-oriented exercises but also fluency-based activities.